Thermal joining of thermoplastic metal hybrids by means of mono- and polychromatic radiation - Amend, P.; Pfindel, S.; Schmidt, Michael (Physics Procedia, 2013)
In recent years, joining of plastics and metals for lightweight constructions has become more and more important for industrial applications. This paper presents a novel approach for thermal joining of thermoplastic metal hybrids by means of a combination of mono- and polychromatic radiation. During this work, hybrid joints of aluminum (EN AW-5182) and technical thermoplastics (PC, PA6, PA66-GF30) are studied. Thereby experiments for transmission and heat-conduction joining are performed. Besides, the influences of laser structuring of the metal surface on the joint connections are investigated. Additionally, climate tests according to BMW PR 308.2 from -30°C to 90°C and from -40°C to 120°C are performed to analyze the long-term durability of the hybrid joint connections. © 2013 The Authors.
Created from Fastlane, Scopus look-up
Keywords: Mono- and polychromatic radiation; Thermal joining; Thermoplastic metal hybrids